Archenemy [videorecording (DVD)] - Mortimer, Adam Egypt; Manganiello, Joe; Brooks, Skylan; Griggs, Zolee; Scheer, Paul, 1976- (Image Entertainment, 2021)
Max Fist claims to be a hero from another dimension who fell through time and space to Earth, where he has no powers. No one believes his stories except for a local teen named Hamster. Together, they take to the streets to wipe out the local drug syndicate and its vicious crime boss known as The Manager.